1994
DOI: 10.1164/ajrccm.149.2.8306041
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength in the elderly. Correlates and reference values. Cardiovascular Health Study Research Group.

Abstract: Maximal inspiratory pressure (MIP) was assessed in 4,443 ambulatory participants of the Cardiovascular Health Study, 65 yr of age and older, sampled from four communities. Maximal expiratory pressure (MEP) was also measured in 790 participants from a single clinic. Positive predictors of MIP included male sex, FVC, handgrip strength, and higher levels of lean body mass (or low bioelectric resistance). Negative predictors were age, current smoking, self-reported fair to poor general health, and waist size. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
248
7
41

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(330 citation statements)
references
References 21 publications
17
248
7
41
Order By: Relevance
“…34 An association between respiratory muscle strength and ventilatory function was previously reported among older subjects. 12,35 Moreover, our data support a link between ageassociated worsening in lung function and age-associated FFM decline.…”
Section: Discussionsupporting
confidence: 76%
“…34 An association between respiratory muscle strength and ventilatory function was previously reported among older subjects. 12,35 Moreover, our data support a link between ageassociated worsening in lung function and age-associated FFM decline.…”
Section: Discussionsupporting
confidence: 76%
“…They observed that individuals with lower peripheral muscle strength showed effective reduction in respiratory muscle strength. There also appears to be a relationship between upper limb muscle strength and RMS as reported by Enright et al 28 in a study with older adults, in which the authors found a positive correlation between RMS and handgrip values.…”
Section: Discussionsupporting
confidence: 54%
“…Various hypotheses have tried to explain this negative correlation. Enright et al 28 suggest that it occurs due to the loss of muscle mass, especially in the diaphragm and accessory respiratory muscles. In contrast, other authors 1 believe there is an increase in abdominal compliance with age that dissipates the pressure generated during forced expiration to lower the MEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aging process is associated with a reduction in the total, diaphragmatic and respiratory accessory muscular mass, as well as with a decline in the work output for a same level of neural stimulation (13). Increased compliance of the abdominal compartment in older subjects can dissipate the generated pressure, notably in the forced expiration, reducing the maximal static pressures.…”
Section: Discussionmentioning
confidence: 99%